The Atmospheric Boundary Layer and the "Gray Zone" of Turbulence: A Critical Review. Issue 13 (29th June 2020) - Honnert, Rachel; Efstathiou, Georgios A.; Beare, Robert J.; Ito, Junshi; Lock, Adrian; Neggers, Roel; Plant, Robert S.; Shin, Hyeyum Hailey; Tomassini, Lorenzo; Zhou, Bowen
Abstract: Recent increases in computing power mean that atmospheric models for numerical weather prediction are now able to operate at grid spacings of the order of a few hundred meters, comparable to the dominant turbulence length scales in the atmospheric boundary layer. As a result, models are starting to partially resolve the coherent overturning structures in the boundary layer. In this resolution regime, the so‐called boundary layer "gray zone, " neither the techniques of high‐resolution atmospheric modeling (a few tens of meters resolution) nor those of traditional meteorological models (a few kilometers resolution) are appropriate because fundamental assumptions behind the parameterizations are violated. Nonetheless, model simulations in this regime may remain highly useful. In this paper, a newly formed gray zone boundary layer community lays the basis for parameterizing gray zone turbulence, identifies the challenges in high‐resolution atmospheric modeling and presents different gray zone boundary layer models. We discuss both the successful applications and the limitations of current parameterization approaches, and consider various issues in extending promising research approaches into use for numerical weather prediction. The ultimate goal of the research is the development of unified boundary layer parameterizations valid across all scales. Key Points: The grid resolution of atmospheric models has become fine enough that are able to partially resolve turbulent motions in the boundary layer This resolution regime comprises the turbulence "gray zone" where the assumptions behind traditional parameterizations are no longer valid We review the current efforts by modelers to overcome the gray zone problem in order to provide useful simulations at high resolutions